Comprehensive Review of Stress and its Consequences (International Journal of Preventive Medicine and Health (IJPMH), 2025)
Stress is a part of everyone’s life, which can notoriously affect physical and mental health at the workplace. It may have both beneficial and harmful effects at different times. The analysis of various methods for managing stress in medical facilities will be the primary focus of this research. Regardless of upbringing, major, family circumstances, or education, being able to manage stress successfully is arguably the most crucial ability for maximising experience and achieving our best work. According to numerous studies of college learners, including those by the American College Health Association (2009), the Chronicle of Higher Education (2008), and The Associated Press (2009), 85% of them report that stress is a significant issue and the primary barrier to success. The stress levels and general wellbeing of health services workers are considerably reduced by managerial measures such as regulating workloads, cooperative management, and fostering a positive work atmosphere. These therapies recognise the importance of the work environment and policy, and emphasise the significance of holistic methods in stress management. The origins, consequences, and symptoms of stress are highlighted in this article, which may help individuals learn alternative, beneficial ways to manage stress.